ANALISIS KINERJA GURU DAYAH DARUSS’DAH COT PUUK KABUPATEN BIREUEN BERDASARKAN KARAKTERISTIK INDIVIDU BUDAYA ORGANISASI DAN PERILAKU KERJA - Amri, Ulil; Syaripuddin, Syaripuddin (LPPM-UNIKI, 2023)
This study analyzes the performance of teachers at Dayah Daruss'dah Cot Puuk in Bireuen District, Aceh Province. The analysis is based on aspects of the individual characteristics of the teacher, the organizational culture of the dayah and work behavior. This type of quantitative research with descriptive and verification methods. While the analysis tool with multiple regression approach. The results of research on 55 Islamic boarding school teachers where data were collected through questionnaires, it is known that the relationship between variables is expressed by the equation: Kj = 4.742 + 0.477 Ki + 0.553 Bo + 0.314 Pk, based on statistical tests stating a). Teacher performance is influenced by individual characteristics (Ki), organizational culture (Bo) and work behavior (Pk) with a contribution of 40.3%. So that there is an influence of 55.7% on variables not examined such as teacher competence, compensation and Dayah leadership factors and work facilities. b). Partially the three variables studied have a significant effect with a positive impact on improving the performance of dayah teachers. And the biggest factor is the influence of the dayah organizational culture variable.